Sago Starch-Lipid Complex Formation under Varying Fatty Acid Concentrations for Emulsion Stability Improvement - Tethool, Eduard Fransisco; Pranoto, Yudi; Raharjo, Sri; Supriyadi, Supriyadi (Biota : Jurnal Ilmiah Ilmu-Ilmu Hayati, 2025)
The amount of fatty acids added is critical in creating starch-lipid complexes, which can affect their formation and properties. To use the complex to stabilize oil-in-water emulsion systems, this study intends to assess the effects of fatty acid concentrations on the effectiveness of starch-lipid complex formation and the properties of the resulting complexes. Ultrasonication was used to produce starch-lipid complexes from sago starch with different fatty acid contents (10, 12.5, 15, 17.5, and 20%) for the study. The results demonstrated that adding fatty acids up to 15% concentration significantly improved the water absorption capacity (WAC). In contrast, increasing the complexing index (CI), relative crystallinity (RC), oil absorption capacity (OAC), and contact angle of sago starch-lipid complexes. When the concentration of fatty acids was raised over 15%, the properties of the starch-lipid complex did not change considerably. A concentration of 15% with CI 67.07%, RC 37.94%, WAC 1.352 mL/g, OAC 1.370 mL/g, contact angle 70.82 °, emulsion capacity 36.72%, and emulsion stability 35.80% was shown to be the optimal amount of fatty acids for the production of sago starch-lipid complex. Emulsion stability and capacity can be maintained using a sago starch-lipid complex with an ideal fatty acid concentration of 15%.